The war's end: 15 August 1945 in NHK's morning dramas from 1966 to 2019. Issue 2 (1st August 2019) - Masuda, Sachiko
NHK's morning dramas, commonly known as asadora, usually focus on the lives of female heroines who cheerfully persevere in the face of adversity. They depict how women have responded to changing times, especially during and after the Asia-Pacific War. Since 2010, asadora have achieved increased popularity, and many of the shows broadcast since 2011 – the year of the Great East Japan Earthquake – have returned to the traditional theme of women during war. This study investigates asadora that depict the war period, focusing on the representation of 15 August 1945 since the format's earliest days in the 1960s. As this study of 15 August scenes in asadora shows, memory of the Asia-Pacific War in Japan changed considerably after the catastrophe of 3/11. By understanding the mechanisms of presenting this specific event in popular media, it is also possible to shed light on the general practices of collective memory in Japan.